2019
DOI: 10.1039/c9ra02544h
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a polypyrrole-based competent bifunctional magnetic nanocatalyst

Abstract: An efficient method to synthesize a magnetic nanocomposite with dual catalytic activities with a synergetic effect between Ag nanoparticles, polypyrrole and TiO2 is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…In the absence of the catalysts, the absorbance peak at 400 nm remains unaltered even after long time of reduction reaction [29]. In contrast, the addition of a suitable amount of the catalyst into the solution inductively decline an immediate decolorization of the 4-nitrophenolate solution and the peak intensity located at 400 nm is successively decreased and another new peak of 4-AP is appeared at 300 nm [74]. Figure 5c and d illustrates the plots of absorbance versus reaction time for the reduction of 4-NP by the meso-KIT-6-Pt and meso-KIT-6-Ag catalysts.…”
Section: Catalytic Hydrogenation Of 4-npmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of the catalysts, the absorbance peak at 400 nm remains unaltered even after long time of reduction reaction [29]. In contrast, the addition of a suitable amount of the catalyst into the solution inductively decline an immediate decolorization of the 4-nitrophenolate solution and the peak intensity located at 400 nm is successively decreased and another new peak of 4-AP is appeared at 300 nm [74]. Figure 5c and d illustrates the plots of absorbance versus reaction time for the reduction of 4-NP by the meso-KIT-6-Pt and meso-KIT-6-Ag catalysts.…”
Section: Catalytic Hydrogenation Of 4-npmentioning
confidence: 99%
“…A short induction period may correlate the coordinative unsaturated surface of Pt and Ag atoms, which promote the chemisorption of 4-nitrophenolate ions. Hence, the mechanism of catalytic conversion is presumed to be a chemisorption of 4-NP and BH − 4 on the surface of the catalyst, thereby activates the distant hydrogen at the first stage, as shown in Scheme 2 [29,74,75]. Prior to chemisorption, NaBH 4 reacts with water to provide surface hydrogen for the reduction reaction.…”
Section: Catalytic Hydrogenation Of 4-npmentioning
confidence: 99%
“…Great efforts have been devoted toward the preparation of CP nanomaterials for the fabrication of miniaturized novel flexible sensor platforms that enable portability and high-density arrays because of using small sample amounts, which offer excellent prospects in sensor nanotechnology for advanced detection systems [21]. Recent studies have demonstrated the synthesis of nanostructured CPs with controlled shape and size, which ranged from lithographic techniques to chemical methods [22][23][24][25][26][27][28][29][30][31][32][33]. Stejskal and coworkers demonstrated synthesizing PANI nanostructures and its derivatives by the chemical oxidative polymerization in water [34][35][36].…”
Section: Synthesis Of Nanostructured Conducting Polymersmentioning
confidence: 99%
“…2 Both the adsorptions of anionic [3][4][5][6][7][8] and cationic dyes 7,[9][10][11] have been reported. They have also been tested as photocatalysts for the dye decomposition [12][13][14] or for the separation of heavy-metal ions [15][16][17] or other pollutants. 18 The composite was applied in photothermal therapy because of its absorption of near-infrared radiation, 19 in microwave absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Both the adsorptions of anionic and cationic dyes , have been reported. They have also been tested as photocatalysts for the dye decomposition or for the separation of heavy-metal ions or other pollutants . The composite was applied in photothermal therapy because of its absorption of near-infrared radiation, microwave absorption, , electromagnetic radiation shielding, magnetorheology, or in the design of new materials for supercapacitor electrodes. The list demonstrates that other than electrical properties of conducting polymers often come to the forefront…”
Section: Introductionmentioning
confidence: 99%